The Impact of Artificial Intelligence on Teacher Education: An Interview with Professor Hannele Niemi from the University of Helsinki - Hannele Niemi; Liu Xiaoxu; Wang Jun; Niu Shuanghong (Jiaoshi jiaoyu xuebao)
Artificial Intelligence (AI) is rapidly driving changes in the field of education, and its application is making a profound impact on teacher education. Professor Hannele Niemi from the University of Helsinki is an expert in teacher education and technology-based learning environments.She believes that AI will accelerate significant changes in the education system, particularly in areas such as curriculum design, learning assessment, and personalized learning support. Through big data analysis, AI can assist teachers in gaining a deeper understanding of students' learning needs, which enables them to provide targeted interventions and fosters the development of students' critical thinking and creativity. In Finland, AI has become a crucial tool in teacher education, supporting the transition of teachers from knowledge transmitters to facilitators of personalized learning. However, the integration of AI in education also presents challenges, such as privacy concerns and ethical dilemmas. Professor Niemi emphasizes that teachers should not only acquire the skills to utilize AI technology but also address issues of fairness to ensure that all students benefit equally. Moreover, the cultivation of AI literacy should be a key component of teacher education, with institutions supporting both teachers and students in coping with the ethical risks that AI may cause. Professor Niemi also highlights that future research should focus on how AI can be better integrated into fields such as personalized learning and teacher professional development.